2022
DOI: 10.1111/jth.15803
|View full text |Cite
|
Sign up to set email alerts
|

A personalized limited sampling approach to better estimate terminal half‐life of FVIII concentrates

Abstract: Introduction Hemophilia A is a bleeding disorder characterized by a deficiency of a coagulation factor VIII and optimally treated using pharmacokinetics (PK)‐guided prophylactic replacement therapy. To decrease patient burden, PK can be estimated from sparse sampling leveraging population PK modeling. However, recommendations for sampling times meant for patients with hemophilia A as a group may not be optimal at the individual level. Objective To evaluate a personalized limited sampling approach (Personalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…1.8 (1.6-2.0) 6.9 (6.8-7.1) 1.0 (0.7-1.2) 9.0 (8.8-9.1) À0.9 (À1.0 to À0.8) 4.9 (4.8-5.0) À1.7 (À2.1 to À1.3) 14.2 (13.9-14. would be to use personalized limited sampling approaches [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.8 (1.6-2.0) 6.9 (6.8-7.1) 1.0 (0.7-1.2) 9.0 (8.8-9.1) À0.9 (À1.0 to À0.8) 4.9 (4.8-5.0) À1.7 (À2.1 to À1.3) 14.2 (13.9-14. would be to use personalized limited sampling approaches [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the current approach beforehand it is not known for which patients this will be the case. A possible solution would be to use personalized limited sampling approaches [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…With great interest, we read the recent paper "A personalized limited sampling approach to better estimate terminal half-life of FVIII concentrates" by Pierre et al 1 This report proposed a brand-new personalized limited sampling approach (LSA) that could predict a next sampling time point along with a more accurate calculation of halflife time of factor VIII (FVIII) concentrates. The results demonstrated that compared with a random sampling approach, the personalized LSA method had lower errors in estimation of FVIII half-life time and the number of samples that below the limit of quantification is quite small (4%).…”
Section: Dear Editormentioning
confidence: 99%